+0  
 
0
178
1
avatar

Slopes of these:

(3,-2)(7,8)

(6,7)(8,-1)

(1,-5)(-2,9)

(-5,2)(-3,-7)

(6,3)(4,9)

(2,-5)(-3,9)

(-1,-7)(5,8)

(8,9)(-5,2)

(-4,-7)(-3,2)

(5,-9)(1,6)

This is only one question on my lesson by thee way.sad

 May 10, 2019

Best Answer 

 #1
avatar+9015 
+3

The slope between  (x1, y1 and  (x2, y2)    \(=\quad\dfrac{{\color{purple}y_2}-{\color{blue}y_1}}{{\color{purple}x_2}-{\color{blue}x_1}}\)

 

 

The slope between  (3, -2 and  (7, 8)    \(=\quad\dfrac{{\color{purple}8}-{\color{blue}-2}}{{\color{purple}7}-{\color{blue}3}}\quad=\quad\dfrac{10}{4}\quad=\quad\dfrac52\)

 

 

The slope between  (6, 7 and  (8, -1)    \(=\quad\dfrac{{\color{purple}-1}-{\color{blue}7}}{{\color{purple}8}-{\color{blue}6}}\quad=\quad\dfrac{-8}{2}\quad=\quad-4\)

 

 

The slope between  (1, -5 and  (-2, 9)    \(=\quad\dfrac{{\color{purple}9}-{\color{blue}-5}}{{\color{purple}-2}-{\color{blue}1}}\quad=\quad\dfrac{14}{-3}\quad=\quad-\dfrac{14}{3}\)

 

 

The slope between  (-5, 2 and  (-3, -7)    \(=\quad\dfrac{{\color{purple}-7}-{\color{blue}2}}{{\color{purple}-3}-{\color{blue}-5}}\quad=\quad\dfrac{-9}{2}\quad=\quad-\dfrac92\)

 

 

The slope between  (6, 3 and  (4, 9)    \(=\quad\dfrac{{\color{purple}9}-{\color{blue}3}}{{\color{purple}4}-{\color{blue}6}}\quad=\quad\dfrac{6}{-2}\quad=\quad-3\)

 

 

Do you see how to do this? Can you do the rest?

 May 10, 2019
 #1
avatar+9015 
+3
Best Answer

The slope between  (x1, y1 and  (x2, y2)    \(=\quad\dfrac{{\color{purple}y_2}-{\color{blue}y_1}}{{\color{purple}x_2}-{\color{blue}x_1}}\)

 

 

The slope between  (3, -2 and  (7, 8)    \(=\quad\dfrac{{\color{purple}8}-{\color{blue}-2}}{{\color{purple}7}-{\color{blue}3}}\quad=\quad\dfrac{10}{4}\quad=\quad\dfrac52\)

 

 

The slope between  (6, 7 and  (8, -1)    \(=\quad\dfrac{{\color{purple}-1}-{\color{blue}7}}{{\color{purple}8}-{\color{blue}6}}\quad=\quad\dfrac{-8}{2}\quad=\quad-4\)

 

 

The slope between  (1, -5 and  (-2, 9)    \(=\quad\dfrac{{\color{purple}9}-{\color{blue}-5}}{{\color{purple}-2}-{\color{blue}1}}\quad=\quad\dfrac{14}{-3}\quad=\quad-\dfrac{14}{3}\)

 

 

The slope between  (-5, 2 and  (-3, -7)    \(=\quad\dfrac{{\color{purple}-7}-{\color{blue}2}}{{\color{purple}-3}-{\color{blue}-5}}\quad=\quad\dfrac{-9}{2}\quad=\quad-\dfrac92\)

 

 

The slope between  (6, 3 and  (4, 9)    \(=\quad\dfrac{{\color{purple}9}-{\color{blue}3}}{{\color{purple}4}-{\color{blue}6}}\quad=\quad\dfrac{6}{-2}\quad=\quad-3\)

 

 

Do you see how to do this? Can you do the rest?

hectictar May 10, 2019

9 Online Users

avatar